2020
DOI: 10.3390/ijerph17103434
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of Watching Videos of Different Durations Showing Urban Bamboo Forests with Varied Structures

Abstract: This study illustrated the physiological and psychological effects of watching videos of different durations showing bamboo forests with varied structures. Physiological indicators, including EEG (electroencephalogram), blood pressure, skin conductance, and pulse, were monitored in 180 Chinese university students (mean age: 20.72 ± 2.56 years) while they were watching bamboo videos. Before and after watching the videos, their psychological indicators, including positive and negative moods, were measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…The factors that affect neural activity are diverse, and in the minute-by-minute changes in EEG display ( Figure 6 ), both the experimental and control groups produced different degrees of change one minute after environmental stimulation. This outcome is consistent with the findings of Wang Yu Xi et al [ 49 ], who observed responses in subjects’ EEG one minute after they viewed a nature video; several studies have found that changes in EEG waves reach stability within five minutes regardless whether live or video stimulation is used [ 49 ], but in our study of minute-by-minute changes in EEG parameters, there was a manifestation of unstable changes in each emotional parameter after five minutes, which may be related to the interference of other factors in real-word stimulations. However, this paper is reluctant to draw conclusive inferences from the limited data available, and more research is required to determine the causes of these discrepancies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The factors that affect neural activity are diverse, and in the minute-by-minute changes in EEG display ( Figure 6 ), both the experimental and control groups produced different degrees of change one minute after environmental stimulation. This outcome is consistent with the findings of Wang Yu Xi et al [ 49 ], who observed responses in subjects’ EEG one minute after they viewed a nature video; several studies have found that changes in EEG waves reach stability within five minutes regardless whether live or video stimulation is used [ 49 ], but in our study of minute-by-minute changes in EEG parameters, there was a manifestation of unstable changes in each emotional parameter after five minutes, which may be related to the interference of other factors in real-word stimulations. However, this paper is reluctant to draw conclusive inferences from the limited data available, and more research is required to determine the causes of these discrepancies.…”
Section: Discussionsupporting
confidence: 93%
“…EEG is used to record changes in electrical waves during brain activity [ 49 ]. It is recorded using neuroharmonic EEG biofeedback techniques [ 50 , 51 ] and widely used as emotional feedback in restorative research [ 52 ]; it is noninvasive to humans.…”
Section: Methodsmentioning
confidence: 99%
“…No se encuentra el origen de la referencia.. Neutral images are used to reduce their emotional impact and, thus, make the measurement of the music and vibrotactile effects clearer, according to [41] [42].…”
Section: Discussionmentioning
confidence: 99%
“…Two videos of one-minute length were created, based on sequences of images that were unassociated with a dramatic action, given that images must be kept as neutral as possible to allow the measurement of the music and vibrotactile effects, according to [41] [42]. One video displayed aerial images of cereal fields at sunset.…”
Section: ) Stimulimentioning
confidence: 99%
“…Bamboo is commonly used for urban landscape greening in Oriental gardens [29]. In recent years, researchers have found that walking in bamboo forests can relieve tension, reduce depression and decrease blood pressure [30,31]. However, in addition to bamboo forests, there are many small bamboo species could be used as ornamental materials in urban greening.…”
Section: Introductionmentioning
confidence: 99%